The Effect of Job Training on Employee Performance PT. XYZ (Karawang Plant) - Fitriani, Imas; Partimah, Partimah; Lesmana, Yanto; Fa’uzobih, Fa’uzobih (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is entitled The Effect of Job Training on Employee Performance at PT.XYZ plant Karawang. The aim of this research is to explain the effect of job training on employee performance at the company. This research uses a form of survey research with the formulation of associative hypotheses carried out on 46 employees as respondents at the company. The data collection technique in this research uses a questionnaire with a Likert measurement scale. The t test can be produced with a calculated t count of 10.828 > t table 1.678, simple linear regression can produce a constant value of 3.039, and a coefficient for variable B of 0.909 and from the results of calculating the coefficient of determination, an r² value of 72% is obtained, meaning that the job training variable has an influence positive impact on the performance of PT.XYZ with calculations using the SPSS program. while the rest is influenced by other variables.